PENGEMBANGAN PEMILIKAN MODAL BERSAMA SARANA PENANGKAPAN (CAPITAL SHARING) DI KALANGAN NELAYAN MISKIN - Wahyono, Ary (P2KK LIPI, 2004)
Over exploitation in northern coast of Java is a crucial problem. Serious efforts are badly needed to reduce this problem. This paper will propose one of the solutions to overcome this problem that is developing a collective capital sharing scheme. The proposal is constructed by two assumptions. The first assumption is that one of the core problems of over fishing is the (over-) density of fishing boats in northern coast of Java. The second and that the boat overdensity is caused by private boat ownership which stimulates fishermen to operate as many boats as possible to take the commons marine resources at maximum level. I will argue that communal capital sharing will reduce this tendency and, to the contrary to the private property practice, it will stimulate the spirit of communalism favouring a more fair and sustainable fishing practices.